Pendidikan yang Memanusiakan Manusia - Esther Christiana (Humaniora, 2013)
Education helps people to perfect her/himself as a human being. Education and being human is an integral part, regardless of what the goal or hope for the future. Humanity becomes an important part of the mission of education. Humans are creatures who have special abilities. All things humans do come from natural gift, perfect gift of the Creator in the form of body, soul, mind, and feelings. The perfection of a human is in the nature of humanity, not in his/her efforts but rather as the Creator’s gift. Human perfection in human dimension exists in human imperfection. The perfection in imperfect body is that it has weaknesses, can feel pain, has the ability and endurance limits. The perfection in vibrant soul is that it is full of passion and fragile and may die prematurely. The perfection in feelings is that it can be angry, sad, disappointed, excited. The perfection in mind is that it can think of things that constructs and ruins, creates and destroys. Education plays roles in human choices, the destruction/development of human, which destroys or builds, which kills or gives life, which creates or destroys. The education that humanizes human is the education of humanity-oriented with the education model developing for the space dimension of the development of humanity towards the highest manifestations of each dimension, space of freedom, and space for personal reflection or group.